Answer :

It is given that the first term of GP is -3.


So, a = -3


It is also given that the square of the second term is equal to its 4th term.


(a2)2 = a4


nth term of GP, an = arn-1


So, a2 = ar; a4 = ar3


(ar) 2 = ar3 a = r = -3


Now, the 7th term in the GP, a7 = ar6


a7 = (-3)7 = -2187


Hence, the 7th term of GP is -2187.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

The product of thRD Sharma - Mathematics

Express <imRS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

Express <imRS Aggarwal - Mathematics

Prove that RS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

The sum of n termRS Aggarwal - Mathematics

If a, b, c, d areRS Aggarwal - Mathematics

Evaluate :
</p
RS Aggarwal - Mathematics

The first term ofRS Aggarwal - Mathematics